Impact of Contact With Nature on the Wellbeing and Nature Connectedness Indicators After a Desertic Outdoor Experience on Isla Del Tiburon - Garza-Terán, Glenda; Tapia-Fonllem, Cesar; Fraijo-Sing, Blanca; Borbón-Mendívil, Daniela; Poggio, Lucía (Frontiers in Psychology, 2022)
Nature connectedness is determined by the representation individuals have about themselves within nature. This concept is often studied in relation to the direct contact individuals have with natural environment, which according to some studies have demonstrated to generate positive effects by fostering a feeling of connecting and bonding with nature, as well as improving their well-being. The main focus of this study was to calculate and assess the relation between Nature Connectedness and well-being of participants. The methodological approach of this research reaches quantitative data comparing results obtained from both samples, as well as correlations between the variables. The sample for this study was composed by two groups of university students (M= 25 years old). Both contrast group (n= 32) and experience group (n=29) filled the questionnaire in two separate moments and in different environments. First data collection moment for both groups was held inside a university classroom. A second moment of data collection was carried out after a month from the first application, having the contrast group answer the questionnaire on a classroom again whilst the experience group responded it during an excursion to Isla Del Tiburon in Northwestern Mexico after performing some recreational activities being totally immersed in a local desertic environment. Questionnaire was composed by a 6 point Likert type scale measuring Nature Connectedness through concepts such as Nature relatedness and Love and care for the natural, as well as Subjective and Psychological Well-being of participants. Results show that both well-being and Nature Connectedness are positively influenced by performing activities out in the natural environment. This work was also conducted in response to the need to understand the full extent of Contact and Connectedness to nature, carrying out an exploratory study in desertic settings when much of the early work centers around the study of these variables in green nature environments.